La jubilación patronal, un derecho no reconocido en el Municipio de Guaranda en el año 2020. - Morejón Morejón, Jhonny Gabriel (2023)
The present investigation called "THE EMPLOYER'S RETIREMENT, AN UNRECOGNIZED RIGHT IN THE MUNICIPALITY OF GUARANDA IN THE YEAR 2020", aims to carry out a detailed study on the violation of inalienable rights of workers, who comply with the legal requirements to be beneficiaries of this right, the municipal entity has not complied; which has caused the existence of legal controversies between former workers of the entity and the Municipality of Guaranda, generating the payment of enormous economic resources in recognition of this unfulfilled right. Employer retirement as a right of workers is regulated in the Labor Code, within article 216, which establishes it as a right in favor of workers or workers subject to the Law as long as they meet certain requirements, such as: having the quality of worker or laborer covered by the Labor Code, and 25 years of service or more. In Ecuador, the estimated age to start working is from 15 years. If this person worked continuously for the same employer, they could retire at age 40. Even if it were an untimely dismissal after 20 years of service, he would be able to be entitled to receive a part of the proportional employer retirement when he was only 35 years old. Within the proposed investigation, a series of questions will be developed, which will allow verifying the information in the Municipal GAD of the Guaranda canton in relation to the cases of workers who have terminated their employment relationship and who have not had their employer's retirement benefit canceled . Considering that the National Court of Justice in the jurisprudence of triple reiteration and that it is of obligatory application has determined that the employer's retirement constitutes an inalienable and imprescriptible right, and it is precisely that based on this 5 jurisprudence many former workers after having elapsed For some time they have demanded judicial recognition of this right. Considering the importance of the legal norm regarding the respect of rights in this investigation, a legal analysis will be carried out on the causes and consequences that led to the breach of this right by the Municipal GAD of the Guaranda canton. Keywords: Employer Retirement, Untimely Dismissal, Judicial Disputes, Inalienable and Imprescriptible Right.